Association between pre-service science teachers’ self-efficacy beliefs and their confidence in physics content - Molefe, Paul; Rankhumise, Mmushetji Petrus; Mafa-Theledi, Olivia Neo (CV. Media Digital Publikasi Indonesia, 2024)
This exploratory study examined the relationship between the knowledge of selected physics concepts from the South African National Senior Certificate curriculum and the self-efficacy beliefs of preservice science teachers. Forty-one preservice physical science teachers between the ages of 16 and 30 enrolled in a higher education institution to earn a Bachelor of Education degree made up the participants. Of these, 56.1% were female and 43.9% were male. Every respondent was a recent high school graduate from South Africa enrolled in a second-year university course on basic physical science. The preservice teachers completed the Science Teaching Efficacy Belief Instrument (STEBI-B) and a teaching confidence ranking scale. A confidence ranking for teaching topics from a typical high school science curriculum was determined by analyzing the data. According to the data analysis, preservice teachers are confident and self-sufficient enough to teach science concepts.